MENYEMAI GAGASAN INKLUSIF FAZLUR RAHMAN - Mubarak Mubarak (AL-Fikr, 2015)
The study of this article is the study of figures. Fazlur Rahman became the central figure of the discussion. One big idea is the idea of photographing inclusive in Islamic thought as well as a subject matter in this article. Fazlur Rahman had a progressive synthesis mindset that has given hitoris in perspective toward Islam and put hermeneutics-objective analysis in exploring the Koran, which later gave birth to a solid footing on a foundation of tradition (orthodox) Islam, and able to get out of the trap of stagnation for contextual spirit and compatible of the these days, namely the Islamic spirit substantive and liberating. In an effort to build it Fazlur Rahman makes hermeneutics as a tool or method in the interpretation of scripture. The first movement consists of two two steps; The first step, to understand the meaning of a statement of the Qur'an, by reviewing historical situation or problem from which the Qur'an answers and responses appear. The second step, to generalize from specific answers, statements-statements that have moral goals-social public, which can be abstracted from specific verses in the light of the historical background and rationale.